Anxiety, depression, psychological stress and coping style in medical postgraduates in southeastern China when restricted to commuting between the campus and hospital during the COVID-19 pandemic - Tan, Tianci; Liu, Wenting; Zhao, Qianqian; Hou, Yanfei; Yang, Yuan; Wu, Xiaxin; Wang, Yuying; Chen, Yu; Hu, Guangli (Frontiers in Psychiatry, 2023)
Background As the COVID-19 epidemic was gradually brought under control, a new autumn semester began in 2020. How was the mental health of postgraduates as they experienced quarantine at home, only commuting between the school and hospital? Methods The research was conducted in a cross-sectional online survey in October 2020. The data were collected from 1,645 medical postgraduates (master’s and doctoral students) by using the demographic information questionnaire, the Self-rating Depression Scale (SDS), the Self-rating Anxiety Scale (SAS), the Questionnaire on Psychological Stressors of Postgraduates (QPSP), the Simplified Coping Style Questionnaire (SCSQ) and the Social Support Rate Scale (SSRS). One-way ANOVA and Pearson correlation were used to explore the relationships among anxiety, depression, psychological stressors, social support and coping style. Structural equation modeling (SEM) was conducted to assess the mediation model. Results Among the total of 1,645 medical postgraduates, 21.6% (n = 356) had self-rated depression symptoms, and 9.4% (n = 155) had self-rated anxiety symptoms. The main disturbances they experienced were employment, academic and interpersonal pressure. The master of third grade students had the highest employment pressure, and the master of second grade students had the highest academic and interpersonal pressure. Negative coping played a negative mediating role and social support played a positive mediating role in the relationships between perceived stress and anxiety (β = 0.027, P < 0.01; β = 0.124, P < 0.01) and depression (β = 0.016, P < 0.01; β = 0.193, P < 0.01). Conclusion Medical postgraduates in China restricted to studies on campus and in the hospital experienced psychological distress. Our results suggest that providing employment and learning guidance, while strengthening social support and guiding positive coping may be effective at improving the mental health of the medical graduate students, mediating their perceived stress and negative emotions.